Intervention of Religion-based Education in Depression Syndrome among Married Women Attending Cultural Centers in Babol - Mohammad Hadi Yadollahpour; Hakimeh Mahdavifar; Ramezan Hasanzadeh (Shahid Beheshti University of Medical Sciences, 2019)
For downloading the full-text of this article please click here. Background and Objective: Today depression is one of the most prevalent psychological disorders and a widespread issue in human life. This study aims to evaluate the effect of teaching Quran and its prominent concepts on depression among married women. Method: The study is experimental including a control group and a pre-test/post-test design. Research population includes all married women between 25 and 45, living in Babol. The randomized sample includes 50 women attending cultural centers divided into experimental and control groups. Married women were trained in ten sessions. The main instrument was a depression questionnaire which had 13 multiple-choice items with a Chronbach's alpha of 0.87. All ethical issues were observed in the study and the researchers declared no conflict of interests. Results: The effect of Quran therapy on depression syndrome among married women of Babol in the experimental group is statistically significant (p<0/05). In other words, by removing the effect of pretest, there is a meaningful difference between the mean of the two groups in pro-test scores. This shows that Quran therapy has a positive and meaningful effect on depression in married women. Conclusion: Reading Quran, using its divine teachings, and being accustomed to this heavenly book, if accompanied by honest practice, can lower depression and increase mental health of married women. Knowing Quran and commitment to Quran therapy and attention to its solutions and teachings need to be taken seriously both in families and throughout our Islamic society. For downloading the full-text of this article please click here.